“The stars move still”: Haste and Delay in Marlowe’s Doctor Faustus - Tyler Dunston (Journal of Marlowe Studies)
Christopher Marlowe’s Faustus exists in a tenuous, even at times tortuous, relationship to time. This essay explores Doctor Faustus’s treatment of impatience and delay in the context of its pacing and its poetics, particularly its use of pentameter. This analysis is part of a larger project on the poetics of suspension in early modern poetry, and as such, it also briefly considers Marlowe in relation to John Donne’s notion of suspension in the context of faith, as well as to William Shakespeare’s portrayal of the tension between haste and delay in figures such as Hamlet, Lady Macbeth, and Macbeth. Marlowe’s Faustus is a particularly fascinating figure for illuminating the symbolic resonances of suspension and delay in early modern English poetry given his changing relationship with time over the course of the play. He is defined by impatience at the outset, going so far as to ask the spirits he is summoning, “Quid tu moraris? [Why do you delay?]” (1.3.20). However, by the end of the play this characterization is not only subverted but inverted—and this inversion echoes Faustus’s inversion of holy rites as well as Marlowe’s own metrical inversions which accompany it. The contrapasso-like twist of the finale of the play is such that, when damnation is at hand, all Faustus can ask for is a suspension of space and time: “Stand still, you ever-moving spheres of Heaven, / That time may cease, and midnight never come” (1.14.65-66). And yet his final request is for his suffering to have a temporal limit, via metempsychosis or some other means. The most frightening thing for Faustus is, in the end, the ultimate form of suspension—eternity.